Analysis of asset growth in relation to profitability and economic benefits members of puspa mekar cooperative - Baihaqqy, Mochammad Rizaldy Insan; Salsabila, Nusuki; Ikhsan, Sugiyanto; Ernawati, Nani; Yuliawati, Yupi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2025)
The purpose of the study is to obtain an overview of the relationship between asset growth and return on assets (ROA) as well as find out what factors affect the ROA at Puspa Mekar KUD and also find out the state of economic benefits for members. The method used in this study is descriptive with a quantitative approach. The variables used are asset growth and profitability ratio, namely ROA and to analyze ROA factors, namely profit margin and total assets turnover (TATO). The data used was obtained from interviews and secondary data in the form of financial statements for the last five years. The results showed that the relationship between asset growth and ROA has a significant influence with a quite strong positive relationship. In addition, it is known that the influencing factors, namely ROA based on profit margin TATO are caused by the use of assets that are less effective and not optimal in controlling the costs of their operational activities. For direct and indirect economic benefits at Puspa Mekar KUD, members do not feel the benefits of price and SHU part of members, but members get many benefits in the form of services, only in the financial service unit members have felt the economic benefits.